De novo construction of an expanded transcriptome assembly for the western tarnished plant bug, Lygus hesperus. Issue 1 (December 2016) - Tassone, Erica; Geib, Scott; Hall, Brian; Fabrick, Jeffrey; Brent, Colin; Hull, J.
Abstract Background The plant bugLygus hesperus Knight is a polyphagous pest of many economically important crops. Despite its pest status, little is known about the molecular mechanisms responsible for much of the biology of this species. EarlierLygus transcriptome assemblies were limited by low read depth, or because they focused on specific conditions. To generate a more comprehensive transcriptome, we supplemented previous datasets with new reads corresponding to specific tissues (heads, antennae, and male reproductive tissues). This transcriptome augments currentLygus molecular resources and provides the foundational knowledge critical for future comparative studies. Findings An expanded, Trinity-basedde novo transcriptome assembly forL. hesperus was generated using previously published whole body Illumina data, supplemented with 293 million bp of new raw sequencing data corresponding to five tissue-specific cDNA libraries and 11 Illumina sequencing runs. The updated transcriptome consists of 22, 022 transcripts (average length of 2075 nt), 62 % of which contain complete open reading frames. Significant coverage of the BUSCO (benchmarking universal single-copy orthologs) dataset and robust metrics indicate that the transcriptome is a quality assembly with a high degree of completeness. Initial assessment of the new assembly's utility revealed that the length and abundance of transcripts predicted to regulate insect physiology and chemosensation have improved, compared with previousL. hesperus assemblies. Conclusions This transcriptome represents a significant expansion ofLygus transcriptome data, and improves foundational knowledge about the molecular mechanisms underlyingL. hesperus biology. The dataset is publically available in NCBI and GigaDB as a resource for researchers.